PROBLEMATIKA GURU DALAM PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS (ABK) SD INKLUSI TAMAN SISWA REJANG LEBONG - Intan, Intan; warsah, Idi; Jaya, Guntur Putra; Jamaludin, Gilang Maulana (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2020)
Children with special needs are those who need education provided according to each individual’s need. They should receive proper education in the same way as other normal children to develop their potential without any discrimination against their backgrounds. Inclusive schools become one of the answers to meet these needs. Many things must certainly be prepared by educational institutions before implementing the inclusive-based school model amid the community because this will be capable of minimizing learning problems in the future. Grounded in this issue, the researcher sought to find out more deeply the problems of implementing an inclusive education at Elementary School of Taman Siswa in Rejang Lebong. This study applied a qualitative approach, and the data were garnered by means of observation, interviews, and documentation. The data were further analyzed using qualitative analysis stages. This study found the following conclusions. The problems faced by teachers in terms of inclusive-school learning are teachers’ competences, no specific tutor for students with special needs, parents' knowledge, students’ difficulties in receiving materials, the readiness of school management, lack of government’s attention and public awareness. The efforts made by the school to overcome these problems include: implementing learning by using fun methods and media, involving students with special needs in each learning activity, providing additional time for students with special needs, and trying to make use of learning facilities individually.